Design of a Solar Power Plant System for Government Buildings in the Ibu Kota Nusantara of Indonesia Using HOMER Optimization - Mohd Afzanizam Mohd Rosli; Abram Anggit Mahadi; Catur Harsito; Singgih Dwi Prasetyo (Mekanika: Majalah Ilmiah Mekanika, 2025)
Indonesia's social and political landscape necessitates a balanced distribution of development and a restructuring of its population and industries. In response, the government has relocated the capital from Jakarta to Ibu Kota Nusantara (IKN) in East Kalimantan, aiming to alleviate the pressures on the central city. Given the region's abundant solar energy resources, this paper explores the potential for investing in solar energy systems within government buildings to align with the innovative city initiative. The study employs the Hybrid Optimization Model for Electric Renewables (HOMER) to evaluate the feasibility of the government's solar energy plan. This simulation tool analyzes investment costs, energy generation potential, and economic viability. The HOMER configuration includes solar panels, batteries, and an inverter integrated with the on-grid electrical system, tailored to meet government building requirements. Simulation results indicate that the proposed model can generate approximately 828,980 kWh annually, with a total energy consumption of around 643,257 kWh. The estimated investment cost is IDR 20,581,290,000, with a production cost of IDR 1,407.11 per kWh and a net payback period of about seven years. This analysis suggests that solar energy systems are well-positioned to thrive in IKN's emerging business environment.